Plants Used for Cosmetics in the Eastern Cape Province of South Africa: A Case Study of Skin Care - Sagbo, Idowu Jonas; Mbeng, Wilfred Otang (Pharmacognosy Reviews)
Cosmetology is the science of change of appearance and has been practiced since ancient times. In South Africa, especially Eastern Cape, the concept of using plants for beautification finds its origin in the traditional medicine literature. Moreover, herbal extract as a whole or part thereof has been used since time immemorial for various ailments of the skin, hair, and for overall appearance. Recently, the interest of consumers in the use of herbal cosmetics has been stimulated by the decline of faith in modern cosmetic products based on the beliefs that herbal cosmetics contain natural ingredients that are less dangerous to the skin and thereby superior to synthetic cosmetics and the reference to successful historical use by different cultures. A number of South African plants have been evaluated for their cosmetic potential. In this article, we reviewed 105 plant species used by the people of Eastern Cape Province for various cosmetic purposes with a majority of them used for skin care (70 species) and dental care (6 species). These plants are distributed in 59 families with the Asteraceae being the most represented with 9 species, followed by Fabaceae (7 species), Asphodelaceae (5 species), Lamiaceae (4 species), Apocynaceae (3 species), Hyacinthaceae (3 species), and other families with two to one species each. The results of the studies conducted confirmed the potential of the Eastern Cape medicinal plants in cosmetic products and identified a number of promising species for further investigation as plant‑based cosmetic agents.
Keywords: Cosmetics; Eastern Cape; herbal cosmetics; plants; skin care; South Africa